Entomological survey to determine the role of cisterns in the production of Aedes aegypti in the U.S. Virgin Islands - Marianyoly Ortiz-Ortiz; Rafael Saavedra-Hernández; Krystal R. Seger; Ryan Hemme; Nicole Marrero-Vázquez; Amaury Morales-González; Warren Ortiz-Ortiz; Tatiana Ortiz-Ortiz; Eduardo Burgos; Roberto Barrera; Grayson Brown; Brett Ellis (PLoS ONE, 2025)
Given the limited potable water supply in the U.S. Virgin Islands, most residents use cisterns to collect rainwater and store it for their daily needs. A survey conducted in 2019 found that 45.7% of the cisterns contained mosquitoes, and 83.3% of the mosquitoes collected were Aedes aegypti, suggesting an important role as mosquito larval development sites. A subsequent entomological survey was designed to determine the importance of cisterns in producing Ae. aegypti mosquitoes and to understand the cistern factors and characteristics that influence productivity. Three floating funnel traps were installed inside each sampled cistern to collect immature mosquitoes, and exit traps were installed on the intake spouts and overflow pipes, when possible, to collect adult mosquitoes. Physical and chemical characteristics were also recorded. Yard and outdoor patio inspections were conducted at participating households to identify other types of containers with immature mosquitoes. A total of 1,858 households were visited, of which 24% granted access to their cisterns for this study. Of these, 76% of cisterns met protocol criteria, which resulted in 342 cisterns being sampled. Approximately half of the cisterns surveyed were positive for immature mosquitoes. A higher percentage was observed on the St. Thomas and St. John islands (STT District, 57.3%) than St. Croix (STX District, 40.9%). Most immature mosquitoes collected were Ae. aegypti (89.2%), followed by Culex spp. (1.3%), and Ae. mediovittatus (0.38%). Pupal surveys revealed that cisterns were the second highest contributor to the production of Ae. aegypti pupae, with 16.9% of the pupae collected from cisterns. However, this number might be underestimated given sampling limitations. Buckets were the highest Ae. aegypti pupal producer with 47.3%. On average, 5.8% of the exit traps installed on cisterns captured adult mosquitoes, with higher rates of capture on the STT district than on the STX (6.4% versus 5.3%, respectively). Most adult mosquitoes collected (90.7%) were identified as Ae. aegypti, while the other 9.2% were Culex spp. We can conclude that cisterns are important larval development sites for Ae. aegypti and vector management strategies must be developed to reduce their impact.